Potensi Sari Buah Nanas (Ananas comosus L. Merr) sebagai Bahan Pengempuk pada Daging Itik Afkir - kalni, roni; Triana, Andi; Aminuddin, Aminuddin (Universitas Gorontalo, 2025)
Ducks are one of the poultry that have great potential to be developed as meat producers and are quite well-known in the community. Local duck products in the form of meat are still not very popular because they are tough and smell fishy. One way to tenderize meat is to coat the meat with bromelain enzyme (protease). This study aims to determine the potential of pineapple juice with different concentrations on the quality of rejected duck meat. Completely Randomized Design (CRD) method with 4 treatments and 4 replications. consisting of P0 (control or no treatment), P1 (15% pineapple juice), P2 (25% pineapple juice) and P3 (35% pineapple juice) with a soaking time of 30 minutes. The parameters observed were pH, Tenderness, Color and Aroma. The results of the study showed that soaking with 35% pineapple juice had a significant effect on the pH and tenderness of the meat of retired ducks, where the pH decreased from 6.41 to 5.51 and the tenderness of the meat was 9.97 kg/cm² to 3.31 kg/cm² with a slightly red color and still smelling fishy.